Planning for Purchasing Decisions and Reporting on Fuel Sales at Gas Stations 34-14108 with the use of Mandiri Cash Management Program at PT. Soemantri Sedoyo - Phamendyta Aldaning Azaria; Ira Yana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
PT.  Soemantri Sedoyo is one of the companies in North Jakarta, precisely on Jalan Surabaya Kav C – 3 KBN Marunda which is engaged in the distribution of retail fuel oil (Pertamina) which manages Public Fuel Filling Stations (SPBU 34-14108).  This study aims to determine the management process in the process of buying and selling fuel by using the available programs, one of which is independent cash management.  The research method with descriptive analysis.  The results of the study show that at the planning stage in this fuel purchase decision, the use of the Mandiri cash management program as a business internet banking service provides access to the company's financial transactions including online payments, receipts and liquidity arrangements.  In addition, Mandiri cash management can be used as a repository for reporting on the results of daily fuel sales.  The storage area for data from company financial expenses and income is in other system programs such as Microsoft Access and Excel.